ChemInform Abstract: 3‐Alkyl‐1, 2‐cyclopentanediones by Negishi Cross‐Coupling of a 3‐Bromo‐1, 2‐cyclopentanedione Silyl Enol Ether with Alkylzinc Reagents: An Approach to 2‐Substituted Carboxylic Acid γ‐Lactones, Homocitric and Lycoperdic Acids. Issue 11 (February 2016) - Paju, Anne; Kostomarova, Diana; Matkevits, Katharina; Laos, Marit; Pehk, Tonis; Kanger, Tonis; Lopp, Margus
Abstract: Product (IIIe) can be converted to give homocitric acid lactone.